2004
DOI: 10.1093/hgs/dch061
|View full text |Cite
|
Sign up to set email alerts
|

Jewish Israeli Teenagers, National Identity, and the Lessons of the Holocaust

Abstract: This article examines the attitudes of a group of Jewish Israeli adolescents who participated in a Holocaust seminar that included an optional trip to related sites in Poland. The authors sought to determine whether youth who participate in such a seminar still consider Jewish Israeli identity important, which lessons of the Holocaust they value, and whether belonging to a survivor's family makes a difference when considering these lessons. The results show that, regardless of participation in the trip and aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…The seemingly contradictory outcomes-anti-social as well as prosocial-that can stem from historical group-based victimization salience beg for an explanation. Like others Lazar et al, 2004), we contend that the emergence of prosocial versus anti-social consequences might be dependent on the type of meaning or lesson that is drawn from the historical ingroup victimization. Klar et al (2013), for example, found that some Jewish-Israelis believe a lesson of the Holocaust is to "never be passive bystander" to others' suffering.…”
Section: Moral Obligation Of Historically Victimized Groupsmentioning
confidence: 75%
“…The seemingly contradictory outcomes-anti-social as well as prosocial-that can stem from historical group-based victimization salience beg for an explanation. Like others Lazar et al, 2004), we contend that the emergence of prosocial versus anti-social consequences might be dependent on the type of meaning or lesson that is drawn from the historical ingroup victimization. Klar et al (2013), for example, found that some Jewish-Israelis believe a lesson of the Holocaust is to "never be passive bystander" to others' suffering.…”
Section: Moral Obligation Of Historically Victimized Groupsmentioning
confidence: 75%
“…In this study, we divided the sample into Holocaust survivors and descendants (Holocaust group) and compared them with the rest of the sample (non‐Holocaust group). We hypothesized that the radicalizing effect of the Holocaust among survivors and descendants is higher among participants with high exposure to contemporary political violence because such violence rekindles a sense of imminent existential threat (Bar‐Tal & Antebi, ) and therefore may blur the distinction between past traumas and contemporary conflict (Lazar et al, ) such that both types of threat become “virtually indistinguishable sources of pain and anger” (Lifton, , p. 2263). Thus, we predicted that, in the Holocaust group, exposure to contemporary violence would be associated with greater political militancy and lower support for compromises for peace and that these associations would be mediated by perceptions of existential threat.…”
Section: Studymentioning
confidence: 99%
“…Because the Holocaust stands as a reminder of Jewish helplessness, it serves as a central justification for Zionist ideology. Indeed, research indicates that participating in trips to Holocaust‐related sites in Poland increase identification with Zionism among third‐generation Israelis and reduces their willingness to contemplate the universal lessons of the Holocaust (Lazar, Chitin, Gross, & Bar‐On, ). From a social representations perspective (Reicher & Hopkins, ), the specific manner in which a historical event is construed elicits particular aspects of social identity that influences responses to the event.…”
mentioning
confidence: 99%
“…This idea is prominent in contemporary Americans' descriptions of their lives where suffering is believed to ultimately bring redemption and fulfillment (Baumeister, 1991;McAdams, 2006). Indeed, victims themselves often report deriving benefits following traumatic experiences including learning what is really important in life and becoming a kinder, more understanding person (Affleck et al, 1987;Bower et al, 2009;Davis et al, 1998;Lazar et al, 2004;Poulin et al, 2009;Taylor, 1983). Witnesses of traumatic events can similarly make meaning of adversity by deriving benefits for the victims, which results in higher expectations that those victims will display tolerance toward others (Fernández et al, 2014).…”
Section: Tragedy Represents a Threat To Belief In A Just Worldmentioning
confidence: 99%